Epidemiology of acute pediatric poisonings complicated by cardiogenic shock - a 6-year study in a clinical toxicology unit - Cristina Daniela Enache; Madalina Elena Petran; Simona Stanca; Viorela Gabriela Nitescu; Coriolan Emil Ulmeanu; Roxana-Elena Bohiltea; Cristina Iolanda Vivisenco (Amaltea Medical Publishing House, 2021)
Background. Acute pediatric poisonings represent an emergency pathology that associates a significant risk of adverse outcome or death. The increased incidence reported by antitoxic centers is a public health problem and requires implementing prevention strategies. Material and method. The six-years study targets children diagnosed with acute poisoning complicated by cardiogenic shock in a pediatric toxicology unit, performing a descriptive analysis of the epidemiological characteristics of the group. Aim. To provide statistical data that can represent the basis of preventive measures carried out by health services. Results. The incidence of severe intentional poisonings complicated by cardiogenic shock is almost twice as high as accidental ones. A strong correlation was identified between intentional poisonings and adolescent girls. Conclusions. The detailed epidemiological data allows targeted intervention measures to prevent suicide attempts and decrease the incidence of accidental exposures among the pediatric population.